The Water Balance of the Alps - What do we need to protect the water resources of the Alps? Proceedings of the Conference held at Innsbruck University, 28-29 September 2006 - Lackner, Reinhard (alpine space - man and environment, 2007)
This book contains the proceedings of the conference "The Water Balance of the Alps. What do we need to protect the water resources of the Alps?" held in Innsbruck in September 2006. The aim of the conference was to present the view of researchers as well as of administrators, and to discuss the best way to protect sensitive waters, including ice and snow, of the Alps. Intensive discussions about the best way to protect sensitive water bodies in the Alps - either by implementing specific and hitherto neglected aspects peculiar to mountain regions into the EU Water Framework Directive or by creating a new Water Protocol for the Alpine Convention - went along with the presentation of fresh views on known water problems.